Colorado day by day - Everett, Derek R., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
This-day-in-history approach to key figures and events that shaped Colorado from the 1690s to the present. A relevant vignette for each day of the calendar year, exploring Colorado's many facets through distilled tales of people, places, events, and trends that shaped, and continue to shape, the region.--Provided by publisher.
Introduction -- January -- February -- March -- April -- May -- June -- July -- August -- September -- October -- November -- December -- Image credits.
Keywords: Colorado -- History -- Chronology; Colorado -- Social life and customs